Pro-resolving lipid mediator Resolvin D1 serves as a marker of lung disease in cystic fibrosis. - Olaf Eickmeier; Daniela Fussbroich; Klaus Mueller; Friederike Serve; Christina Smaczny; Stefan Zielen; Ralf Schubert (PLoS ONE)
Background Cystic fibrosis (CF) is an autosomal recessive genetic disorder that affects multiple organs, including the lungs, pancreas, liver and intestine. Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) locus lead to defective proteins and reduced Cl- secretion and Na+ hyperabsorption in the affected organs. In addition, patients suffering from CF display chronic inflammation that contributes to the pathogenesis of CF. Recent work suggests that CF patients have a reduced capacity to biosynthesize specialized pro-resolving lipid mediators (SPMs), which contributes to the development and duration of the unwanted inflammation. Alterations in the metabolism of arachidonic acid (AA) and docosahexaenoic acid (DHA) to specialized pro-resolving mediators (SPMs), like lipoxins (LXs), maresins (MaRs), protectins (PDs) and resolvins (Rvs), may play a major role on clinical impact of airway inflammation in CF. Methods In this study, our aims were to detect and quantitate Resolvin D1 (RvD1) in sputum and plasma from patients with CF and compare levels of RvD1 with biomarkers of inflammation and lung function. We studied 27 CF patients aged 6 to 55 years (median 16 years) in a prospective approach. Results DHA can be found in the plasma of our CF patients in the milligram range and is decreased in comparison to a healthy control group. The DHA-derived pro-resolving mediator Resolvin D1 (RvD1) was also present in the plasma (286.4 ± 50 pg/ mL, mean ± SEM) and sputum (30.0 ± 2.6 pg/ mL, mean ± SEM) samples from our patients with CF and showed a positive correlation with sputum inflammatory markers. The plasma concentrations of RvD1 were ten times higher than sputum concentrations. Interestingly, sputum RvD1/ IL-8 levels showed a positive correlation with FEV1 (rs = 0.3962, p< 0.05). Conclusions SPMs, like RvD1, are well known to down-regulate inflammatory pathways. Our study shows that the bioactive lipid mediator RvD1, derived from DHA, was present in sputum and plasma of CF patients and may serve as a representative peripheral biomarker of the lung resolution program for CF patients.